Total Factor Productivity Industri Mikro dan Kecil di Kawasan Timur Indonesia - Manganti, Marella Dea; Budyanra, Budyanra (UI Scholars Hub, 2025)
The Micro and Small Industries (MSIs) sector, part of non-oil and gas processing industry, is a key driver of the Indonesia’s economy. However, in Eastern Indonesia (EI), the number of industries and workers in the MSIs sector does not match the level of output, unlike in Western Indonesia, where the industry is more stable and aligned. This difference is mainly due to variations in technological progress, known as Total Factor Productivity (TFP). This study analyzes TFP in the MSIs sector across provinces in EI from 2013 to 2022 using panel data regression. Results show that South Sulawesi has the highest TFP, while East Nusa Tenggara has the lowest. The study found that the Fixed Effect Model was the best model, with variables like guidance/training, wages, and infrastructure having a significantly positive impact on MSIs’s TFP.